Diatomita manifestations's dispositions and description, Tunja-Chivatá's sector (2007)
Arising from the investigation project titled "The diatomite industrial Use's evaluation, Tunja-Chivatá, sector", with the support of Colciencias and the pedagogic and technological university of Colombia it was carried out a geologic recognition in the municipalities of Tunja, Chivatá and Siachoque. It comprises: The specific area of interest convered by a field direct work; an analysis of aerial photography and dentification of the different emerging geologic units, plus a pilot deposit of Diatomeas. New areas of interest with the mineral presence were identified, in total thirteen deposits denominated satellites in th study area. Departing from the physical chemical characterization, the out cropping lithic aspects were described. In the same way the geologic context is denoted for each one of them. Among the most significant achievements are pointed out the identification of eight deposits in the municipality of Siachoque, up to now not mentioned, with interesting characteristics for their benefit and use. Their physical, chemicals and topographical aspects and accidents show a feasible continuity among the different emerging deposits. Market by the base level of the river Tocavita and Cormechoque, a minor interruption is observed, due to the erosion inside the deposit area, followed by a deposit of the quaternary era.